2019
DOI: 10.18632/oncotarget.26574
|View full text |Cite|
|
Sign up to set email alerts
|

Transforming growth factor β-induced epithelial-to-mesenchymal signature predicts metastasis-free survival in non-small cell lung cancer

Abstract: Transforming growth factor beta (TGFβ) plays a key role in regulating epithelial-to-mesenchymal transition (EMT). A gene expression signature (TGFβ-EMT) associated with TGFβ-induced EMT activities was developed using human Non-Small Cell Lung Carcinoma (NSCLC) cells treated with TGFβ-1 and subjected to Affymetrix microarray analysis. The final 105-probeset TGFβ-EMT signature covers 77 genes, and a NanoString assay utilized a subset of 60 of these genes (TGFβ-EMTN signature). We found that the TGFβ-EMT and TGFβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Wang et al provide evidence that enhanced expression of pELAV1/Hur and SNAI1 cellular markers of mesenchymal transition are associated with reduced survival in patients with conventional treatment. These findings are consistent with earlier studies that have identified more classical markers of mesenchymal transition as markers for reduced survival (22) and resistance to EGFR inhibitor therapy (23), including VIM, SNAI1, ECDH and others in human non-small cell cancers. The explanations for reduced survival in patients with EMT signature positive cancers may be related to enhanced motility and chemotherapy resistance characteristic of the mesenchymal state.…”
supporting
confidence: 92%
“…Wang et al provide evidence that enhanced expression of pELAV1/Hur and SNAI1 cellular markers of mesenchymal transition are associated with reduced survival in patients with conventional treatment. These findings are consistent with earlier studies that have identified more classical markers of mesenchymal transition as markers for reduced survival (22) and resistance to EGFR inhibitor therapy (23), including VIM, SNAI1, ECDH and others in human non-small cell cancers. The explanations for reduced survival in patients with EMT signature positive cancers may be related to enhanced motility and chemotherapy resistance characteristic of the mesenchymal state.…”
supporting
confidence: 92%
“…To understand the expressions of PLK1 during NSCLC metastasis, we leveraged a published transcriptome of several NSCLC cells treated with TGF-β to induce the EMT (GSE 114761) [27] (Fig. 1d).…”
Section: T210 Of Plk1 Is Highly Phosphorylated In Tgfβ-induced Emt Bmentioning
confidence: 99%
“…DEPTOR was also identified as one of the 77 clinically relevant predictive biomarker at TGFβ-EMT signature generated by microarray analysis of TGFβ-1 treated non-small cell lung cancer cells. TGFβ-EMT gene signature could predicted overall survival and metastasis-free survival in lung adenocarcinoma [26]. MASP-2 (Mannan-binding lectin-associated serine protease 2) is a plasma protein involved in lectin pathway of complement system which promotes cell differentiation, proliferation, migration and reduced apoptosis.…”
Section: Discussionmentioning
confidence: 99%